Phthalocyanines bearing silazane group for colorectal cancer - GÖRGÜLÜ, AHMET ORHAN; YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT; SALAN, ÜMİT (ELSEVIER SCI LTD, 2021)
The synthesis of bis(trimethylsilyl)amine substituted zinc(II), and indium(III) chloride phthalocyanine complexes have been performed. The obtained compounds were characterized by spectroscopic methods. All synthesized phthalocyanine derivatives were evaluated for cytotoxic, genotoxic, and apoptotic activities on LoVo cell lines which are the standard colorectal cancer cell lines derived from metastatic site: left supraclavicular region. Nonperipheral silazane substituted zinc phthalocyanine (5) showed quite different behavior from all the other compounds analyzed and found to be the best cytotoxic, genotoxic, and apoptotic compound. All derivatives showed no proliferative effect at all doses. All phthalocyanine compounds increased cytotoxicity, DNA damage, apoptosis, and intracellular ROS dose-dependent manner. To explain and verify in vitro tests, phthalocyanine compound structures were optimized using density functional theory, and in silico molecular docking studies on B-DNA dodecamer were performed. Both the experimental and theoretical findings comply with each other.
Keywords: Silazane phthalocyanine; Pharmacokinetic; LoVo cell; Colorectal cancer; DNA binding; PHOTODYNAMIC THERAPY; CARBONIC-ANHYDRASE; COLON-CANCER; DNA-DAMAGE; APOPTOSIS; ZINC(II); PHOTOSENSITIZER; PERFORMANCE; DERIVATIVES; ANTICANCER